AFPs: How Are the Owners Doing? Return on Equity of the AFPs (Observatorio Económico, 2009)
One of the virtues of the current regulation of the individual capitalization (defined-contribution) system is that the returns obtained by the owners of the AFPs (pension fund administrators) closely track those obtained by members. Continue reading...
Keywords: AFP; profitability